ORGANIZATION OF BALANCED SCORECARD SYSTEM IN THE MANAGEMENT ACCOUNTING OF THE ENTERPRISE - Ibrokhimjon U. Tursunaliev (Galaxy International Interdisciplinary Research Journal, 2024)
This thesis explores the organization of the Balanced Scorecard (BSC) system within the framework of management accounting, aiming to provide insights into its implementation, effectiveness, and impact on organizational performance within a specific enterprise context. Adopting a mixed-methods approach, the research combines qualitative interviews and quantitative surveys to gather data from key stakeholders within the organization. Qualitative data are analyzed thematically, while quantitative data undergo statistical analysis, enabling a comprehensive understanding of the research questions. The study reveals positive perceptions regarding the effectiveness of the BSC in improving organizational performance. Quantitative analysis establishes a statistically significant positive correlation between the alignment of the BSC and organizational goals. However, challenges in implementation, such as a resistance to change, highlight the complexity of integrating the BSC into management accounting practices. The positive findings underscore the potential benefits of a well-implemented BSC in enhancing organizational performance and strategic alignment. Challenges identified emphasize the need for strategic considerations in addressing issues related to organizational culture and resistance to change. The research has implications for both theory and practice, emphasizing the importance of a customized BSC implementation to suit the unique organizational context. It underscores the need for organizations to proactively address challenges in the implementation process to fully leverage the potential benefits of the BSC. Future research should delve deeper into specific aspects, such as the long-term impact of BSC implementation, the role of leadership, and comparative analyses across industries. Exploring the applicability of the BSC in different organizational sizes and sectors could provide a more comprehensive understanding of its effectiveness in diverse contexts. In conclusion, this thesis contributes valuable insights into the organization of the Balanced Scorecard system within management accounting practices. It emphasizes the importance of aligning performance measurement systems with organizational goals for sustained success, offering practical implications for organizations seeking to optimize their strategic performance measurement practices.